Nurses’ Knowledge and Attitudes towards Prevention of Pressure Ulcers - Beáta Grešš Halász (International Journal of Environmental Research and Public Health, 2021)
Background: Pressure ulcers (PU) remain a serious complication of immobile patients and a burden for healthcare professionals. The incidence and prevalence remain alarming. Knowledge and attitudes of nurses play a fundamental role in prevention. The aim of this study was to determine the knowledge and attitudes of nurses towards the prevention of PU in selected Slovak hospitals and find relationships and differences among selected variables. Methods: A quantitative exploratory cross-sectional design was chosen. Validated instruments were used. From the 460 randomly selected nurses, 225 (49%) participated in this research. Results: Results showed insufficient knowledge (45.5%) and attitudes (67.9%) of nurses towards PU prevention. There was a significant positive correlation found between the knowledge and attitudes (ρ = 0.300; p = 0.000). Nurses´ knowledge was significantly different within the level of education (p = 0.031) and work department (p = 0.048). Conclusions: Results showed insufficiencies in the knowledge and attitudes of nurses towards PU prevention. Therefore, it is essential to focus on general education and continuing education and practice of nurses. Further development of educational programs and frequent measurement of these two parameters can lead to a significant improvement in the quality of care provided.